2016
DOI: 10.1016/j.dcn.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal functional connectivity and episodic memory in early childhood

Abstract: Episodic memory relies on a distributed network of brain regions, with the hippocampus playing a critical and irreplaceable role. Few studies have examined how changes in this network contribute to episodic memory development early in life. The present addressed this gap by examining relations between hippocampal functional connectivity and episodic memory in 4-and 6-year-old children (n=40). Results revealed similar hippocampal functional connectivity between age groups, which included lateral temporal region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 70 publications
(131 reference statements)
12
64
4
Order By: Relevance
“…In adults, this method does not elicit significant differences in hippocampal connectivity in comparison to a standard fixation resting-state scan, providing preliminary evidence that a non-canonical resting-state scan may be used to tap the hippocampal network without eliciting significantly altered connectivity [see Supporting Information; Greicius et al, 2003;Riggins et al, 2016;Vanderwal et al, 2015]. 2 There were no significant differences in results when left-handed participants were excluded.…”
Section: Data Acquisitionmentioning
confidence: 91%
“…In adults, this method does not elicit significant differences in hippocampal connectivity in comparison to a standard fixation resting-state scan, providing preliminary evidence that a non-canonical resting-state scan may be used to tap the hippocampal network without eliciting significantly altered connectivity [see Supporting Information; Greicius et al, 2003;Riggins et al, 2016;Vanderwal et al, 2015]. 2 There were no significant differences in results when left-handed participants were excluded.…”
Section: Data Acquisitionmentioning
confidence: 91%
“…Specifically, functional connectivity between the hippocampus and cortical regions was influenced by age and performance. These studies also suggested that functional connectivity between the hippocampus and regions not typically thought to relate to memory formation in adults decreased developmentally (i.e., the orbital frontal gyrus and left and right middle temporal gyrus in Geng et al, ; the right inferior frontal gyrus in Riggins et al, ).…”
Section: Evidence For Relations Between Neural Development and Memorymentioning
confidence: 96%
“…Two studies have explored relations between task‐free hippocampal functional connectivity and memory ability assessed outside the MRI scanner in young children (Geng et al, ; Riggins, Geng, Blankenship, & Redcay, ). Findings from both studies were similar to those from task‐based fMRI studies.…”
Section: Evidence For Relations Between Neural Development and Memorymentioning
confidence: 99%
“…In adolescents and adults, but not children, the volume of the anterior hippocampus as well as functional activation of the anterior hippocampus and prefrontal cortex predict better associative memory performance (DeMaster et al, 2014). Critically, research investigating pre-adolescent development have detailed increases in associative memory processes as well as changes in connectivity between the hippocampus and prefrontal cortex (Riggins, Geng, Blankenship, & Redcay, 2016). However, the extant evidence above shows that these processes approach adult levels in adolescence.…”
Section: Neurobehavioral Evidence Of the Refinement Of Integrated mentioning
confidence: 99%